Effects of pH, UV-B radiation and NaCl on anthocyanin stability from vivid blue petals of Clitoria ternatea L., a potential natural colourant from legume crop - Mahmad, Noraini; Taha, Rosna Mat (Emerald, 2018)
Purpose: The purpose of this study is to investigate the effects of pH, UV-B radiation and NaCl on anthocyanin extracted from vivid blue petals of Clitoria ternatea L. (legume crop), as a potential natural colourant for food, dye or coating technology. Design/methodology/approach: The anthocyanin from petals of Clitoria ternatea was extracted using 0.5 per cent trifluroacetic (TFA) in methanol solution. The liquid colourant was exposed to different pH (1, 4.5 and 5.5), UV-B radiation and sodium chloride (NaCl). The results were compared using UV-vis spectrophotometric analysis. Findings: Anthocyanins are sensitive and quickly degrade in the presence of light. In the dry powder form, the anthocyanin is easier to maintain and preserve (storage). Research limitations/implications: Anthocyanins extracted from vivid blue petals of Clitoria ternatea L. are sensitive and quickly degrade in the presence of light. Practical implications: The anthocyanin pigments extracted from Clitoria ternatea L. petals with methanolic acid were successfully coated on glass slides. The combination of binders and pigments had produced environmental paint which added with stabilisers (additives) for better durability. Acrylic has been known for its high weathering and embrittlement resistance, good mechanical and electrochemical properties and gloss retention. Social implications: This anthocyanin is suitable as natural colourant especially in baby products, cosmetics production or for coating and varnish application. Originality/value: Till date, the natural colourant of Clitoria ternatea L. petals is widely used in food. However, this result is a new finding, as there is no report on the potential of applications of this natural colourant for coating technology. Therefore, the current study with appropriate extraction method was significantly based on the relevant literatures of coating production from pigment by using other plant species. The findings and conclusion highlight the practicality as the potential applications in coating technology.